Talent Management System at I.N. Ulianov Сhuvash State University - A. Yu. Aleksandrov (Высшее образование в России)
Involving the talented youth in the processes of innovation development is an important factor in the development of the society and modernization of the Russian economy. The national education system defines working with gifted children and young people as a key priority. The role of universities in youth talents training and management increases inasmuch the purpose of educational institutions is not only training of specialists with the highest professional qualification but creating the so-called intellectual elite of the country as well. The model of talent management system functioning at I.N. Ulianov Chuvash State University is described in the article. The article examines the complex multi-level system presented by interaction between elements «school – higher education provider – production». The basic forms of identifying and following up gifted schoolchildren and students and forms of supporting young lecturers are considered. A number of the University structural subdivisions such as Centre for working with the gifted youth, Center of Supplementary Education, Vocational Guidance Center, Innovation-implementation Center take part in working with talents by implementing a year-round complex of events. One of the key factors in functioning the talent management system is staffing. With a view to maintaining continuity, fostering young teachers’ motivation the University implements in-house target programs. One of the most effective forms of preserving and transferring the best practices of professional adaptation is tutorship. A multilevel approach makes it possible to create conditions for maximum revealing talents in students, professionals and to build the system of continuity within the system of working with young talents.